Elevating Profitability: The Roles of Innovation, SG&A Expenses, Capital Structure and Production Costs - yunus, Naviel; Cacik Ruth Damayanti; Nur Imamah (The International Journal of Accounting and Business Society, 2025)
Purpose — This study investigates the impact of research and development expenses, selling, general and administrative expenses (SG&A), production cost, and financial leverage on Indonesia's manufacturing sector profitability. Specifically, the impact of research and development expenses on firm profitability.. Design/methodology/approach—This research relies on Indonesian manufacturing’s financial statements listed on the Indonesian Stock Exchange from 2017 to 2022 and implements Warp PLS 3.0 for hypothesis testing and path diagram creation. Findings—The results show that research and development expenses significantly influence firm profitability, whereas SG&A expenses show a contrary finding. These results provide evidence of the important role of research and development in increasing company value. Practical implications—More investment in R&D and innovation could potentially attract more investors to Indonesian manufacturing companies. Originality/value—This paper examines whether investment in marketing, research and development in Indonesia is more beneficial for firms in Indonesian manufacturing companies. It is expected that this analysis will give significant insight into future company budgeting policies for both R&D and SG&A expenses.